Behavioral and electrophysiological investigation of hearing and speech outcomes in pre-linguistic deaf children with white matter changes after cochlear implantation. (2nd December 2019) - Shen, Min; Chen, Zhongyan; Li, Yuan
Abstract: Background: There are some debates regarding the benefit from cochlear implantation (CI) for prelingually deaf children with white matter changes. Objective: To assess the hearing and speech outcomes of prelingually deaf children with white matter changes (group A), and those with complete deafness (group B), at 2 years after CI. Material and Methods: Study 1 included 32 and 34 children in group A and B, respectively. The Categories of Auditory Performance (CAP) and Speech Intelligibility Rate (SIR) were used to assess the performance on hearing and speech. Study 2 included eight children with white matter changes and eight with complete deafness at 2 years post-CI, and nine normal-hearing peers. The mismatch response (MMR) to the stimulus pair 'ba'/'pa' was investigated. Results: There was no significant difference on CAP or SIR scores between the children in group A and B. All children with white matter changes showed MMRs to Mandarin consonants at 2 years post-CI. And there was no significant difference on the incidence, the latency or amplitude of MMR among three groups. Conclusions and significance: Most prelingually deaf children with white matter changes got good outcomes from CI. CI is not a contraindication for most individuals with white matter changes.